Karakterisasi Dan Potensi Pemanfaatan Ekstrak Pelepah Kelapa Sawit Menjadi Bioetanol - May Kristina; David Andrio; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Oil Palm Frond (OPF) extract is the largest biomass in the palm oil industry. Fresh oil palm frond extract can be readily obtained by just pressing the fresh OPF. Oil palm frond extract contains of high sugar concentrations such as glucose, making it a potential medium for bioethanol fermentation. This research was conducted by analyzing the characteristics of OPF through glucose, pH, chemical oxygen demand (COD) and volatile suspended solid (VSS) as well as its potensial in producing bioethanol. The glucose content in the OPF extract was 37 g/L, total and soluble COD in OPF 56,000 mg / L and 48,000 mg / L, VSS amounting to 2,133 mg / L and pH 5. This result indicates that OPF extract can be used as a renewable feedstock for bioethanol production.Keywords: Oil Palm Frond (OPF) extract, Bieothanol fermentation